Enhancing ASPP2 promotes acute liver injury via an inflammatory immunoregulatory mechanism - Zhang, Xiangying; Xu, Ling; Fan, Zihao; Gao, Yao; Tian, Yuan; Cao, Yaling; Chen, Dexi; Ren, Feng (Frontiers in Immunology, 2024)
Background Acute liver injury (ALI), which is a type of inflammation-mediated hepatocellular injury, is a clinical syndrome that results from hepatocellular apoptosis and hemorrhagic necrosis. Apoptosis stimulating protein of p53-2 (ASPP2) is a proapoptotic member of the p53 binding protein family. However, the role of ASPP2 in the pathogenesis of ALI and its regulatory mechanisms remain unclear.The expression of ASPP2 were compared between liver biopsies derived from patients with CHB, patients with ALI, and normal controls. Acute liver injury was modelled in mice by administration of D-GalN/LPS. Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. ASPP2-knockdown mice (ASPP2 +/-) were used to determine its role in acute liver injury. Mouse bone marrow macrophages (BMMs) were isolated from wildtype and ASPP2 +/-mice and stimulated with LPS, and the supernatant was collected to incubate with the primary hepatocytes. Quantitative real-time PCR and western blot were used to analyze the expression level of target.The expression of ASPP2 was significantly upregulated in the liver tissue of ALI patients and acute liver injury mice. ASPP2 +/-mice significantly relieved liver injury through reducing liver inflammation and decreasing hepatocyte apoptosis.Moreover, the conditioned medium (CM) of ASPP2 +/-bone marrow-derived macrophages (BMMs) protected hepatocytes against apoptosis. Mechanistically, we revealed that ASPP2 deficiency in BMMs specifically upregulated IL-6 through autophagy activation, which decreased the level of TNF-α to reduce hepatocytes apoptosis. Furthermore, up-regulation of ASPP2 sensitizes hepatocytes to TNF-αinduced apoptosis.Our novel findings show the critical role of ASPP2 in inflammatory immunoregulatory mechanism of ALI and provide a rationale to target ASPP2 as a refined therapeutic strategy to ameliorate acute liver injury.